2000
DOI: 10.1021/ma9911389
|View full text |Cite
|
Sign up to set email alerts
|

Structural Ordering in Phenyl-Substituted Polythiophenes

Abstract: Various substituted poly(phenylthiophene)s have been studied by X-ray diffraction. They are semicrystalline, with very different degrees of crystallinity. Those with para-substituted phenyl groups have a low degree of crystallinity, whereas those with ortho-substituted phenyl groups are more crystalline. The most crystalline materials in this study have two equally long substituents on the phenyl ring, one at the ortho position and the other at the ortho or meta position on the opposite side of the phenyl ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
58
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 15 publications
13
58
0
Order By: Relevance
“…The optimized cell axis are the same for PEDOT:PSSH and the two doped structures. The repeat unit of the PEDOT chain is calculated to be 7.7-7.8 Å, and the lattice parameter which determines the distance between the chains stacked on top of each other is found to be 6.9 Å, Both these values agree with previously reported experimental results [27][28]. The separation between the PEDOT chains increases from 3.56 Å in the pure PEDOT structure, to 3.83 Å in PEDOT:PSSH, and to 3.82 Å in the two doped structures.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The optimized cell axis are the same for PEDOT:PSSH and the two doped structures. The repeat unit of the PEDOT chain is calculated to be 7.7-7.8 Å, and the lattice parameter which determines the distance between the chains stacked on top of each other is found to be 6.9 Å, Both these values agree with previously reported experimental results [27][28]. The separation between the PEDOT chains increases from 3.56 Å in the pure PEDOT structure, to 3.83 Å in PEDOT:PSSH, and to 3.82 Å in the two doped structures.…”
Section: Resultssupporting
confidence: 89%
“…A periodic PEDOT structure was built guided by the distances given for PEDOT doped with tosylate [27] and with PF 6 [28]. The geometry optimized structure (cell axes and coordinates are optimized) of the PEDOT polymer is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The way that the molecules order in the solid phase is of great importance as for example in the case of P3HT which orders in a lamellar structure. [67][68][69][70][71][72] …”
Section: Other Factorsmentioning
confidence: 99%
“…For a chemically and electronically very similar polythiophene, poly͓3-͑4Ј-octylphenyl͒thiophene͔ ͑POPT͒, which also shows comparable orange and blue phases, x-ray studies proved that the blue phase of this polymer has a considerable higher degree of crystallinity than the orange phase 13 and recent x-ray studies on PEOPT suggested the same trend. 14 In their blue phase the conformation of these polymers results in a much stronger interchain interaction ͑ stacking, aggregates͒ thereby causing the shift of the HOMO-LUMO levels. A similar phenomenon was observed recently for other regioregular polythiophenes.…”
Section: B Excited-state Spectroscopymentioning
confidence: 99%
“…12 For a series of regioregular substituted poly͑3-phenylthiophenes͒ this phenomena of two different phases was studied extensively by x-ray diffraction. 13,14 In general, the class of substituted poly͑3-phenylthiophenes͒ is semi- A highly interesting phenomena is observed for many of the poly͑3-phenylthiophenes͒ with a para substitution of the phenyl ring. Depending on the processing conditions, spin-coated thin films of these polymers can exist in two distinct states with different crystallinity: a less crystalline state with a larger spacing of the highest occupiedlowest unoccupied molecular orbital ͑HOMO-LUMO͒ distance and a higher crystalline state with a lower HOMO-LUMO distance.…”
Section: Introductionmentioning
confidence: 99%